PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SQUARE (TPSq) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMAN 12 PADANG - Zahira, Syakira Gema (Departemen Matematika, 2023)
Understanding of mathematical concepts is one of the learning objectives of mathematics that must be mastered by students. However, based on the result of test in SMAN 12 Padang, it is known that students’ understanding of mathematical concept is still low. The solution to overcome this problem is to apply the Think Pair Square (TPSq) cooperative learning model. The purpose of this study was to describe the development of student’s understanding of mathematical concept during the application of TPSq cooperative learning model and to analyze and describe whether the student’s understanding of mathematical concepts who learn with TPSq cooperative learning model is better than those who learn with direct learning model in class XI MIPA SMAN 12 Padang. This type of research is a quasi-experimental with the The Non-equivalent Posttest-Only Control Group Design. Sampling was conducted using Simple Random Sampling technique, and selected class XI MIPA 5 as the experimental class while class XI MIPA 6 as the control class. Based on the results of data analysis, it can be concluded that students’ understanding of mathematical concept who learn with TPSq cooperative learning model is better than those who learn with direct learning model in class XI MIPA SMAN 12 Padang.Kata Kunci - Understanding of Mathematical Concepts, Think Pair Square (TPSq)